PENGARUH PERPUTARAN KAS, PERPUTARAN PERSEDIAAN, PERPUTARAN PIUTANG, DAN DEBT TO EQUITY RATIO TERHADAP PROFITABILITAS PERUSAHAAN (Studi Pada Perusahaan Food and Beverages Yang Terdaftar di Bursa Efek Indonesia Periode 2013-2017) - Safina Komalasari, 15.05.51.0333; Irsad, Moch. (Students' Journal of Economic and Management, 2019)
This study axamined the effect of Cash Turnover, Inventory Turnover, Receivable Turnover and Debt to Equity Ratio to Profitability at manufacturing business in Indonesian stock axchange period 2013-2015. The population in this research was sub sector of Food and Beverages Companies listed in Indonesian Stock Exchange. The samples with predetermined criteria were 64 Food and Beverages companies that went public on the Indonesia Stock Exchange. The sampling technique used was Purposive Sampling Method or sampling technique with certain considerations or criteria during 2013-2017, so the number of samples (n) = 64. While the method used is Multiple Regression Analysis. The test result showed that the Cash Turnover has negative and not significant influence on Profitability, Inventory Turnover has positive and not significant influence on Profitability, Accounts Receivable has negative and not significant influence on Profitability and Debt To Equity Ratio has negative and significant influence on Profitability.